Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
All real numbers are solutions.
Step-by-step explanation:
Let's solve your equation step-by-step.
−3(x−14)+9x=6x+42
Step 1: Simplify both sides of the equation.
−3(x−14)+9x=6x+42
(−3)(x)+(−3)(−14)+9x=6x+42(Distribute)
−3x+42+9x=6x+42
(−3x+9x)+(42)=6x+42(Combine Like Terms)
6x+42=6x+42
6x+42=6x+42
Step 2: Subtract 6x from both sides.
6x+42−6x=6x+42−6x
42=42
Step 3: Subtract 42 from both sides.
42−42=42−42
0=0
Answer:
all real numbers
Step-by-step explanation:
-3 (x - 14) + 9x = 6x + 42
-3 (x - 14) + 9x - 6x = 6x - 6x + 42
-3 (x - 14) + 3x = 42
-3 (x) - 3 (-14) + 3x = 42
-3x + 42 + 3x = 42
3x - 3x + 42 = 42
42 = 42
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.